2015
DOI: 10.36469/9903
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Fidaxomicin for the Treatment of Clostridium Difficile Infection (C. difficile-associated diarrhoea) in Ireland

Abstract: Background: Clostridium difficile is associated with 20–30% of cases of antibiotic-associated diarrhoea. The incidence of C. difficile infection (CDI) is higher in Ireland than in other countries in Europe, and it is associated with considerable morbidity. Previously recommended standard therapeutic options were vancomycin and metronidazole, but the macrocyclic antibiotic fidaxomicin has recently been recommended for use in adults with CDI in Ireland. Objectives: To perform a cost-utility analysis of fidaxomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Of the 13 EEs reported as full publications, six [ 26 , 27 , 46 , 58 , 62 , 65 ] had previously been presented at a conference [ 38 , 41 , 45 , 52 , 63 , 66 ] and posters were sourced for all except one [ 45 ]. For the remaining EEs, the data were reported in abstract ( n = 7) [ 36 , 39 , 49 , 53 , 54 , 56 , 57 , 59 ] or poster form ( n = 7) only [ 40 , 43 , 44 , 47 , 51 , 60 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 EEs reported as full publications, six [ 26 , 27 , 46 , 58 , 62 , 65 ] had previously been presented at a conference [ 38 , 41 , 45 , 52 , 63 , 66 ] and posters were sourced for all except one [ 45 ]. For the remaining EEs, the data were reported in abstract ( n = 7) [ 36 , 39 , 49 , 53 , 54 , 56 , 57 , 59 ] or poster form ( n = 7) only [ 40 , 43 , 44 , 47 , 51 , 60 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vancomycin was assessed in all 27 EEs, whereas fidaxomicin and metronidazole were investigated in 24 EEs [ 26 28 , 36 , 37 , 39 , 40 , 42 , 43 , 46 51 , 54 , 56 – 60 , 62 , 64 ] and 13 EEs [ 37 , 44 , 46 49 , 51 , 54 , 55 , 57 , 59 , 62 , 65 ], respectively. In two EEs [ 37 , 57 ], vancomycin and metronidazole were combined in a single treatment arm and the intervention used was based on CDI severity or C. difficile strain.…”
Section: Resultsmentioning
confidence: 99%
“…A US study from the third-party payer perspective found that fidaxomicin may be a more cost-effective option for the treatment of CDIs compared with vancomycin under most scenarios tested [ 34 ]. In addition, a recent cost-utility analysis from an Irish Health Service Executive perspective showed that fidaxomicin was dominant to vancomycin or metronidazole for the treatment of CDI [ 19 ]. Finally, a cost-utility study from the Spanish National Health Service perspective showed that the treatment of CDI with fidaxomicin would be cost-saving and lead to improved quality of life when compared with vancomycin in patients with cancer, renal impairment, or treated with concomitant antibiotics [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following health state utility values [ 27 ] were used in the model: 0.33 per cycle for patients with CDI; 0.56 for patients treated successfully (first cycle, 10 days) after the end of treatment; 0.78 for successfully treated patients (second and subsequent cycles after the end of treatment); and 0.78 for patients without CDI. Due to a lack of available CDI-specific utility data, the data utility source used was not disease-specific; however, these utility data have been used in other published cost-effectiveness and cost-utility CDI models [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation